PEMBEKALAN TEKNIK ALGORITMA DALAM KEAMANAN DATA ERA REVOLUSI INDUSTRI 4.0 - Anwar, Nizirwan; Mulyani, Erry Yudhya; Ummanah, Ummanah (Universitas Esa Unggul, 2020)
Allah SWT created humans on earth as sosial beings to interact or communicate with each other (correspondence / collaboration). And along with the exponential development of information and communication technology, it has changed the mindset and attitude and the way of communicating in the virtual world of sosial networking pages via cyberspace. With the aim of gaining comfort, sharing ideas, calm, creative and innovative collaborations that are constructive in correspondence or user-generated content. In computer security, there are several important aspects of Confidentiality, so that the data on the device does not fall into unauthorized